RESPONSIBILITY FOR CONTROL; ETHICS OF PATIENT PREPARATION FOR SELF-MANAGEMENT OF CHRONIC DISEASE - Redman, Barbara K. (Bioethics, 2007)
Patient self-management (SM) of chronic disease is an evolving movement, with some forms documented as yielding important outcomes. Potential benefits from proper preparation and maintenance of patient SM skills include quality care tailored to the patient's preferences and life goals, and increase in skills in problem solving, confidence and success, generalizable to other parts of the patient's life. Four central ethical issues can be identified: 1) insufficient patient/family access to preparation that will optimize their competence to SM without harm to themselves, 2) lack of acknowledgement that an ethos of patient empowerment can mask transfer of responsibility beyond patient/family competency to handle that responsibility, 3) prevailing assumptions that preparation for SM cannot result in harm and that its main purpose is to deliver physician instructions, and 4) lack of standards for patient selection, which has the potential to exclude individuals who could benefit from learning to SM. Technology assessment offers one framework through which to examine available data about efficacy of patient SM and to answer the central question of what conditions must be put in place to optimize the benefits of SM while assuring that potential harms are controlled.